Implementation of Teachers in Developing Student Responsibilities Through Online Learning in Elementary Schools: Implementasi Guru Dalam Mengembangkan Tanggung Jawab Siswa Melalui Pembelajaran Daring Di Sekolah Dasar - Arianti, Divia; Kurniawan, Machful Indra (Indonesian Journal of Education Methods Development, 2021)
This study aims to develop the character of responsibility in online learning. This research was conducted because there are still many children who are not responsible for example in doing assignments, mastering materials and collecting materials. This research uses a qualitative approach. Data collection is in the form of observation, interviews and documentation. The results of this study indicate that in developing the character of students' responsibility in schools through online learning well. Although there are some responsibility constraints experienced by students in submitting assignments late. Therefore, instilling character to foster good behavior in students, teachers must set an example to their students, especially responsible behavior so that children can become firm and punctual individuals in doing assignments. The responsibility of a teacher to students is to be a good teacher in science and character development, so that children have superior potential. Keywords: character of responsibility, online learning